2020
DOI: 10.3389/fevo.2020.00077
|View full text |Cite
|
Sign up to set email alerts
|

Kith or Kin? Familiarity as a Cue to Kinship in Social Birds

Abstract: Interacting with relatives provides opportunities for fitness benefits via kin-selected cooperation, but also creates potential costs through kin competition and inbreeding. Therefore, a mechanism for the discrimination of kin from non-kin is likely to be critical for individuals of many social species to maximize their inclusive fitness. Evidence suggests that genetic cues to kinship are rare and that learned or environmental cues offer a more parsimonious explanation for kin recognition in most contexts. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 105 publications
(167 reference statements)
3
17
0
Order By: Relevance
“…Further investigation into the learning and development of vocal cues in situations where there are multiple potential tutors is a worthwhile avenue for further study. Familiarity is the most widely supported mechanism of kin recognition in cooperatively breeding birds (71,72), with kin association during extended brood care providing the sensitive period during which reliable recognition templates can form (7). In long-tailed tits, it is very likely that first-order kin are associated during this crucial period, but there are instances in which this is not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation into the learning and development of vocal cues in situations where there are multiple potential tutors is a worthwhile avenue for further study. Familiarity is the most widely supported mechanism of kin recognition in cooperatively breeding birds (71,72), with kin association during extended brood care providing the sensitive period during which reliable recognition templates can form (7). In long-tailed tits, it is very likely that first-order kin are associated during this crucial period, but there are instances in which this is not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Early-life associations can be a cue for kin discrimination (e.g. [17]) and lead to strong preferences later in life [18][19][20][21]. For example, newborn pipistrelle bats (Pipistrellus kuhlii) raised in separate groups for six weeks preferred to associate with and groom familiar conspecifics and heterospecifics after being released into a common flight cage [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Relatedness and familiarity are often inherently linked within siblings due to their shared raising environment and are difficult to tease apart (Leedale et al, 2020): even when studies have found evidence that siblings preferentially associate over unrelated individuals, they rarely separate genetic relatedness from more simple cue-based familiarity (e.g. Bonadonna and Sanz-Aguilar, 2012; Kurvers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%